The Effect of Low-Dose Atropine on Alpha Ganglion Cell Signaling in the Mouse Retina - Wang, Qin; Banerjee, Seema; So, ChungHim; Qiu, ChunTing; Sze, YingHon; Lam, Thomas Chuen; To, Chi-Ho; Pan, Feng (Frontiers in Cellular Neuroscience, 2021)
Low-dose atropine eye drops are had been applied to control myopia progression, especially in children. However, the impact of atropine on the retina is unclear. Mass spectrometry detected atropine in the retina after external ocular application. However, the application of atropine did not change the morphology and firing pattern of most retinal ganglion cells. Atropine unmasked inhibition to induce ON responses from certain OFF RGCs, possibly via the GABAergic pathway in the retina circuit. The results suggest that although atropine can reach the retina via the application of low-dose atropine eye drops, its presence did not change the spike frequency of the ON and OFF αRGCs. However, it may interfere with retinal signal processing in around one-fourth of OFF αRGCs.